Use of optical properties for evaluating the presence of pyrogenic organic matter in thermally altered soil leachates. Issue 4 (17th February 2020) - McKay, Garrett; Hohner, Amanda K.; Rosario-Ortiz, Fernando L.
Abstract : Optical measurements reveal the presence of pyrogenic organic matter in laboratory heated soil leachates, indicating their potential for application in field measurements. Abstract : The increased frequency and severity of wildfires in forested watersheds has the potential to significantly impact the quantity and quality of water extractable organic matter (WEOM) exported from these ecosystems. This study examined the optical properties of WEOM from laboratory heated soil in order to understand physicochemical changes occurring in the organic matter as a result of heating, as well as test the usefulness of optical parameters for assessing the presence of pyrogenic organic matter. WEOM absorbance and fluorescence spectral shape and intensity varied systematically as a function of soil heating temperature. Notably, absorbance and fluorescence intensity, specific ultraviolet absorbance, apparent fluorescence quantum yield, specific fluorescence emission intensity, and maximum fluorescence emission wavelength exhibited consistent changes with heating temperature and indicated that WEOM in heated soil leachates was lower in molecular weight and more aromatic than in unheated samples. The lower molecular weight in heated soil WEOM was corroborated with size-exclusion chromatography measurements. This work increases the understanding of the molecular changes occurring in WEOM as a result of wildfire and indicates that optical measurements ( i.e., absorbance and fluorescence) could be used for watershed monitoring of post-fire pyrogenic organic matter.